2014
DOI: 10.1021/jp505344a
|View full text |Cite
|
Sign up to set email alerts
|

Solvent Effects on Isotope Effects: Methyl Cation as a Model System

Abstract: The isotopic sensitivity (CH3(+) vs CD3(+)) of the equilibrium between the methyl cation in vacuum and in solution has been investigated. Two alternative options for describing the shape of the solute cavity within the widely used polarized continuum model for implicit solvation were compared; the UFF and UA0 methods give equilibrium isotope effects (EIEs) that vary as a function of the dielectric constant in opposite directions. The same isotope effect was also obtained as the average over 40 structures from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 32 publications
1
21
0
Order By: Relevance
“…It is possible that factors other than compression along the methyl donor–acceptor axis may contribute, at least partially, to the intriguing KIE variations for COMT and its mutant structures. It has already been shown that 2° KIEs are very sensitive to the local dielectric constant 9. Certainly, the present results for a model methyl transfer strongly indicate the necessity for explicit inclusion of CH⋅⋅⋅O interactions in the QM region and Hessian in any new QM/MM simulations of these KIEs for COMT‐catalyzed methyl transfer 17.…”
supporting
confidence: 52%
“…It is possible that factors other than compression along the methyl donor–acceptor axis may contribute, at least partially, to the intriguing KIE variations for COMT and its mutant structures. It has already been shown that 2° KIEs are very sensitive to the local dielectric constant 9. Certainly, the present results for a model methyl transfer strongly indicate the necessity for explicit inclusion of CH⋅⋅⋅O interactions in the QM region and Hessian in any new QM/MM simulations of these KIEs for COMT‐catalyzed methyl transfer 17.…”
supporting
confidence: 52%
“…The D 3 isotope effect for the transfer of methyl cation from vacuum to water, evaluated as an average over 40 solvent configurations (each a locally relaxed snapshot from a hybrid AM1/TIP3P molecular‐dynamics simulation at 298 K), is 0.85; the closest water molecules in both the axial and equatorial directions in these QM/MM structures are located at C⋅⋅⋅O distances ranging from 2.95 to 3.20 Å (i.e. close to the sum of the van der Waals radii).…”
Section: Figurementioning
confidence: 89%
“…It is possible that factors other than compression along the methyl donor–acceptor axis may contribute, at least partially, to the intriguing KIE variations for COMT and its mutant structures. It has already been shown that 2° KIEs are very sensitive to the local dielectric constant . Certainly, the present results for a model methyl transfer strongly indicate the necessity for explicit inclusion of CH⋅⋅⋅O interactions in the QM region and Hessian in any new QM/MM simulations of these KIEs for COMT‐catalyzed methyl transfer .…”
Section: Figurementioning
confidence: 99%
“…This review has covered a broad spectrum of applications and practice related to the science of eggs, and in particular those of laying hens. Numerous factors have been shown to affect eggshell structure and color, implicating fields from enzyme reactivity to calcite formation (Wilson and Williams, 2015 ; Wilson et al., 2015 ; Leitch et al., 2016 ; Wilson and Williams, 2016 ). It has, however, been noted that a substantial number of questions remain in fully understanding the avian egg; the precise chemical formation of the crystalline structure of the eggshell, the distribution of pores, and processes behind termination of calcification all remain relatively unknown.…”
Section: Conclusion and Future Researchmentioning
confidence: 99%